2016
DOI: 10.20961/jkb.v17i9.740
|View full text |Cite
|
Sign up to set email alerts
|

Pendampingan Pengolahan Pangan Lokal Di Desa Keloran Wonogiri

Abstract: <p>Desa Keloran Kecamatan Selogiri merupakan salah satu kecamatan di Kabupaten Wonogiri. Meskipun hasil singkong di  daerah ini  tidak sebanyak daerah lain, namun desa ini memiliki potensi yang menjanjikan sebagai penghasil tanaman ubi  kayu (singkong). Singkong biasanya hanya ditanam di lahan kebun belakang rumah warga. Hasil panen singkong dari kebun lebih sedikit dan biasanya hanya diolah menjadi gaplek untuk dikonsumsi sendiri, jika peralatan memadai para ibu rumah tangga akan mengolah singkong menja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The result showed that application of NAA 0.5 combined with paclobutrazol 1 ppm did not increase the plantlet number (Figure 4a), but improved plantlets more vigorous (Figure 4b). This result is in line with previous research results [10,8]. We hope that improving the vigorous of plantlet could be more easily acclimatized, but unfortunately the plantlet acclimatization was still not succeeded yet.…”
Section: Somatic Embryos Formation and Planlet Vigoroussupporting
confidence: 92%
See 1 more Smart Citation
“…The result showed that application of NAA 0.5 combined with paclobutrazol 1 ppm did not increase the plantlet number (Figure 4a), but improved plantlets more vigorous (Figure 4b). This result is in line with previous research results [10,8]. We hope that improving the vigorous of plantlet could be more easily acclimatized, but unfortunately the plantlet acclimatization was still not succeeded yet.…”
Section: Somatic Embryos Formation and Planlet Vigoroussupporting
confidence: 92%
“…Addition of jasmonic acid 10 µm and sucrose 11 percent in MS containing NAA 0.5 ppm was the highest multiplication rate [7]. Application of IAA 0.5 ppm and paclobutrazol produced healthy and survival [8], it might be correlated to plantlet vigorous. This research used local garlic variety namely Lumbu Kuning to observe induction and multiplication of callus, embryo somatic and plantlet formation, and preliminary test of bulblet in vitro in the greenhouse.…”
Section: Introductionmentioning
confidence: 90%
“…Receiving assistance on packaging elements, Brem's products are quite acceptable to the market, although still on a small scale. Assistance in the marketing aspect Karyanta & Triharyanto (2016), in community service programs is a very important activity to help people know how to market products.…”
Section: Resultsmentioning
confidence: 99%